Cemented carbide insert with eta-phase core
Patent Information
- Application Number
- JP2023577883
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-06-16
- Filing Date
- 2022-06-14
- Publication Date
- 2025-04-23
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a cemented carbide insert in tools for rock drilling, mineral cutting, oil drilling and for concrete and asphalt grinding. [Background technology]
[0002] Cemented carbide has a unique combination of high modulus of elasticity, high hardness, high compressive strength, high resistance to wear and friction, and good levels of toughness, which is why they are commonly used in products such as mining tools.
[0003] EP 0182759 discloses a cemented carbide body comprising a core of cemented carbide containing eta phase surrounded by a surface zone of cemented carbide free of eta phase, with a low content of binder phase at the surface and a higher content of binder phase adjacent to the eta phase zone. The eta phase core provides wear resistance and in combination with the binder phase gradient contributes to the toughness of the insert. These inserts are highly wear resistant and resistant to premature crack formation that would cause the insert to fail prematurely.
[0004] It is also known that cemented carbide mining inserts are commonly treated with edge deburring and case hardening processes, such as tumbling and post-sintering centerless grinding. In case hardening processes, compressive stresses are introduced into the mining insert. The presence of compressive stresses improves the fatigue resistance and fracture toughness of the mining insert. As a result, the threshold energy required to fracture the mining insert is higher, thus reducing the likelihood of chipping, cracking, and / or fracturing of the components.
[0005] However, inserts containing eta-phase surrounded by a surface zone of eta-phase-free cemented carbide with a low binder phase content at the surface and a higher binder phase content adjacent to the eta-phase zone are too brittle to be treated by high energy case hardening processes that can introduce higher levels of compressive stresses. Although an increase in compressive stress can be achieved from a high energy case hardening process, this increase is offset by a high rate of insert chipping and a low yield due to the introduction of micro-damage during processing.
[0006] It would therefore be desirable to be able to provide a cemented carbide insert that combines the benefits of an eta-phase core with improved compositions for improved fracture toughness in a manner that does not result in high levels of chipping. Summary of the Invention
[0007] The disclosure therefore provides a method for treating a cemented carbide insert for rock drilling and mineral cutting, comprising a cemented carbide core and a surface zone of cemented carbide surrounding said core, characterized in that both the surface zone and the core contain WC (α phase) with a binder phase (β phase) based on at least one of cobalt, nickel or iron, the core further contains η phase, the surface zone is free of η phase, an inner part of the surface zone located next to the core has a binder phase content greater than the nominal content of the binder phase in the cemented carbide body, the binder phase content gradually increasing in the surface zone in a direction towards the core by at least 1.2 times compared to the nominal content of the binder phase of the cemented carbide body, and the mining insert is subjected to a surface hardening process carried out at an elevated temperature of 50°C or higher, preferably at a temperature of 100°C or higher, preferably at a temperature of 200°C or higher, more preferably at a temperature between 200°C and 450°C.
[0008] Advantageously, the high temperature surface hardening process produces inserts with improved fracture toughness without the problem of a high percentage of chipped inserts, which often occur in areas of high stress concentration, such as the transition zone between the cylinder and the dome, as well as the transition zone at the bottom of the insert, which reduces production yields. Using this method, high levels of compressive stress are introduced into the cemented carbide mining inserts. The increased tumbling temperature increases the toughness of the cemented carbide, so that impacts do not produce defects such as microcracks, large surface cracks, or chipping of the edges. The higher levels of compressive stress, combined with reduced impact defects, improve the fatigue resistance and fracture toughness of the insert, resulting in longer insert life. A further advantage of this method is that insert geometries such as sharp bottom radii, which previously had low yields due to their susceptibility to excessive damage at the corners, can be tumbled without damaging the edges. This opens up the possibility of developing insert products with various geometries that were not previously suitable for tumbling. This method also allows the use of cemented carbide compositions that were previously too brittle, for example in mining applications or in the high energy tumbling process described in U.S. Patent No. 7,258,833 to Epiroc Smith. The ability to introduce higher levels of compressive stress means that drilling inserts with higher hardness can be used, which is beneficial for increasing the wear resistance and therefore the overall performance of the insert, by increasing the toughness of the drilling insert to an acceptable level.
[0009] Another aspect of the present disclosure is a cemented carbide insert for rock drilling and mineral cutting, comprising a cemented carbide core and a surface zone of cemented carbide surrounding said core, both the surface zone and the core containing WC (α-phase) with a binder phase (β-phase) based on at least one of cobalt, nickel or iron, the core further containing η-phase, the surface zone being free of η-phase, an inner part of the surface zone located next to the core having a binder phase content greater than the nominal binder phase content in the cemented carbide body, the binder phase content gradually increasing in the surface zone in a direction towards the core by at least 1.2 times compared to the nominal binder phase content of the cemented carbide body, the cemented carbide insert having a profile hardness HV3p measured 0.3 mm from the surface along an upper non-cylindrical portion of the cemented carbide insert and an η-phase hardness HV3η which is the average of the HV3 hardness measurements taken in the core η-phase zone, p -HV3 η is more than 20, preferably HV3 p -HV3 η is more than 30, preferably HV3 p -HV3 η More preferably, the hard metal insert has a σ of greater than 40, and even more preferably greater than 50.
[0010] Advantageously, these inserts have high crush strength and improved operational performance, thereby reducing premature insert chipping that previously led to failure.
[0011] Another aspect of the present disclosure is a cemented carbide insert for rock and mineral cutting produced by the method disclosed above or below. [Brief description of the drawings]
[0012] [Figure 1] FIG. 13 is a plot showing the positions of indentations of HV3p and HV3η. [Diagram 2] FIG. 1 is a diagram of HV3 hardness profile. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The cemented carbide body of the present invention has a region containing finely and uniformly distributed η phase embedded in a normal α+β phase structure created in the center of the cemented carbide body. At the same time, the cemented carbide body has a peripheral surface zone containing only α+β phase. The η phase is a type of carbide that is composed of M6C carbides and M 12 This refers to low carbon phases of the WC-Co system, such as C carbides, and phases with the approximate formula M4C. The surface zone is completely free of eta phase. A zone free of eta phase can be produced, for example, by adding carbon at high temperature to a cemented carbide body containing eta phase throughout. By varying the time and temperature, a zone free of eta phase and of the desired thickness can be obtained.
[0014] By "hardmetal" is meant herein a material comprising at least 50% by weight of WC, optionally other hard constituents common in the art of making hardmetals, and a metal binder phase, preferably selected from one or more of Fe, Co, and Ni. In one embodiment of the method, the hardmetal mining insert contains a hard phase comprising at least 80% by weight, preferably at least 90% by weight of WC.
[0015] The metal binder of the cemented carbide can contain other elements that are dissolved in the metal binder during sintering, such as W and C from WC. Depending on the other types of hard constituents present, other elements can also be dissolved in the binder.
[0016] Surface hardening is defined as any process that introduces compressive stresses into the material by physical impact, resulting in deformation hardening at and below the surface, e.g., tumbling or shot peening. Surface hardening is performed after sintering and grinding. Unexpectedly, it has been found that treating the mining insert with a surface hardening process at high temperature reduces or eliminates carbide-to-carbide impact damage in terms of chipping and micro-fracture, and therefore improves product life. The surface hardening process of the present invention is performed at high temperature, which is defined herein as the temperature of the mining insert at the start of the surface hardening process. The upper temperature limit at which the surface hardening process is performed is preferably below the sintering temperature, more preferably below 900°C. The temperature of the mining insert is measured by any method suitable for measuring temperature, such as infrared temperature measurement.
[0017] In one embodiment of the present invention, the mining insert is subjected to a surface hardening treatment at a temperature between 150 and 250°C, preferably at a temperature between 175 and 225°C.
[0018] In one embodiment of the present invention, the upper limit of the surface hardening treatment is 700°C, preferably 600°C, more preferably 550°C.
[0019] In one embodiment of the present invention, the mining insert is subjected to a surface hardening treatment at a temperature between 300 and 600°C, preferably between 350 and 550°C, more preferably between 450 and 550°C.
[0020] The temperature is measured on the mining insert using any suitable method for measuring temperature. Preferably, an infrared temperature measuring device is used.
[0021] In one embodiment, the cemented carbide comprises the hard constituents in a metal binder phase, the content of the metal binder phase in the cemented carbide being between 4 and 30% by weight, preferably between 5 and 15% by weight. The content of the binder phase should be high enough to provide a robust behavior of the mining insert. The content of the metal binder phase is preferably below 30% by weight, preferably below 15% by weight. If the content of the binder phase is too high, the hardness and wear resistance of the mining insert will decrease. The content of the metal binder phase is preferably above 4% by weight, more preferably above 6% by weight.
[0022] In one embodiment, the metal binder phase comprises at least 80% by weight of one or more metal elements selected from Co, Ni and Fe. Preferably Co and / or Ni, most preferably Co, even more preferably between 3-20% by weight Co. Optionally, the binder is a nickel-chromium alloy or a nickel-aluminium alloy. The carbide mining insert may also optionally comprise a grain refiner compound in an amount of up to 20% by weight of the binder content. The grain refiner compound is suitably selected from the group of carbides, mixed carbides, carbonitrides or nitrides of vanadium, chromium, tantalum and niobium. The remainder of the carbide mining insert is made up of one or more hard phase components.
[0023] In one embodiment, the cemented carbide additionally comprises Cr in an amount such that the Cr / binder mass ratio is between 0.043 and 0.19, preferably between 0.075 and 0.15, more preferably between 0.085 and 0.12.
[0024] The Cr / binder mass ratio is calculated by dividing the weight percentage (wt%) of Cr added to the powder blend by the weight percentage of the binder in the powder blend, the weight percentage being based on the weight of that component compared to the total weight of the powder blend. Although Cr dissolves in the binder phase to a significant extent, some amount of chromium carbide may be present in the hardmetal body undissolved, for example up to 3 wt%. However, it may be preferred to add only Cr up to the aforementioned Cr / binder mass ratio so that all of the Cr dissolves in the binder, so that the sintered hardmetal body does not contain undissolved chromium carbide. If the Cr / binder mass ratio is too low, the positive effect of Cr will be too small. On the other hand, if the Cr / binder mass ratio is too high, the formation of chromium carbide concentrations in which the binder dissolves will increase, thereby reducing the volume of the binder phase, and as a result the hardmetal body will become too brittle. The present invention allows the Cr content to be increased before embrittlement becomes an issue.
[0025] Cr is typically added to powder blends in the form Cr3C2 since it has the highest ratio of Cr per gram of powder. 26 It should be understood that alternative chromium carbides such as C2, Cr7C3, or chromium nitrides may be used to add to the powder blend.
[0026] The addition of Cr also improves the corrosion resistance of the cemented carbide body. The presence of Cr also makes the binder more likely to transform from fcc to hcp during drilling, which is beneficial in absorbing some of the energy generated during drilling operations. Thus, the deformation hardens the binder phase, reducing the wear of the button during its use. The presence of Cr increases the wear resistance of the cemented carbide and enhances its deformation hardening ability.
[0027] Apart from the hard phase formers, binders, and Cr-containing components, incidental impurities may also be present in the WC-based starting materials.
[0028] In one embodiment, the content of the binder phase in the surface zone increases towards the core by 1.4 to 2.5 times the nominal content of the binder phase.
[0029] In one embodiment, the grain size of the η phase is 0.5 to 10 μm.
[0030] In one embodiment, the content of the η phase in the core is 2 to 60 volume %.
[0031] In one embodiment, the width of the eta phase core is 10-95% of the diameter of the body.
[0032] In one embodiment, the width of the outermost region with low binder phase content is 0.2 to 0.8 of the width of the region without eta phase.
[0033] In one embodiment, the method includes heating the mining insert and media prior to a hardfacing process, the hardfacing process being performed on the heated mining insert.
[0034] The mining insert can be heated in a separate step prior to the step of the hardfacing process. Several methods can be used to create high temperatures in the mining insert, such as induction heating, resistance heating, hot air heating, flame heating, preheating on a hot surface in an oven or furnace, or using laser heating.
[0035] In an alternative embodiment, the mining insert is kept heated during the hardfacing process, for example using an induction coil.
[0036] In one embodiment, the surface hardening process is tumbling. The tumbling process can be centrifugal or vibratory. A "standard" tumbling process is typically performed using a vibratory tumbler, such as a Reni Cirillo RC650, where about 30 kg of inserts are tumbled at about 50 Hz for about 40 minutes. An alternative typical "standard" tumbling process is to use a centrifugal tumbler, such as an ERBA-120, with a closed lid on top and a rotating disk on the bottom. Another method is a centrifugal barrel finishing process. In both centrifugal processes, the rotation causes the inserts to collide with other inserts or with any added media. In "standard" tumbling using a centrifugal tumbler, the tumbling operation is typically performed from 120 RPM for at least 20 minutes. Lining of the tumbler may also result in the formation of oxides or metal deposits on the surface of the inserts.
[0037] The term "bulk" as used herein means the innermost (center) portion of the cutting tool, which is the zone having the lowest hardness in this disclosure.
[0038] A high energy tumbling (HET) process may be used to introduce higher levels of compressive stress into the cemented carbide mining insert. There are many different possible process settings that can be used to introduce HET, including the type of tumbler, the amount of media added (if any), the processing time, and the process settings, such as the RPM of a centrifugal tumbler. Therefore, the most appropriate way to define HET is in terms of "any process setting that introduces a certain degree of deformation hardening into a homogeneous cemented carbide mining insert made of WC-Co, having a mass of about 20 g." In this disclosure, HET is defined as a tumbling process that introduces a hardness change, measured using HV3, after tumbling (ΔHV3%) of at least the following: ΔHV3%=9.72-0.00543*HV3 bulk (Formula 1) During the ceremony, ΔHV3%=100*(HV30.3mm -HV3 bulk ) / HV3 bulk (Formula 2)
[0039] HV3 bulk is the average of at least 30 impact points measured at the innermost (center) part of the cemented carbide mining insert, HV3 0.3mm is the average of at least 30 indentation points 0.3 mm below the tumbling surface of the cemented carbide mining insert. This is based on measurements made on cemented carbide mining inserts with uniform properties. "Uniform properties" means that after sintering, the hardness differs by no more than 1% from the surface zone to the bulk zone. The tumbling parameters used to achieve the deformation hardening described in equations (1) and (2) on a uniform cemented carbide mining insert would be applied to a cemented carbide body with gradient properties.
[0040] HET tumbling may typically be performed using an ERBA120 having a disk size of about 600 mm operated at about 150 RPM when the tumbling operation is performed either without media or with media larger in size than the insert being tumbled, or about 200 RPM when the size of the media used is smaller than the insert being tumbled, and may be performed using a Rosler FKS04 tumbler having a disk size of about 350 mm operated at about 200 RPM when the tumbling operation is performed either without media or with media larger in size than the insert being tumbled, or about 280 RPM when the size of the media used is smaller than the insert being tumbled. Typically, the parts are tumbled for at least 40-60 minutes.
[0041] In one embodiment, after the mining insert has been subjected to a hardfacing process at high temperature, the mining insert is subjected to a second hardfacing process at room temperature. Advantageously, this removes debris and oxides, e.g., iron oxide, that accumulate on the insert surface from the inside of the treatment vessel. The second hardfacing process, which is carried out at room temperature, can be carried out in wet conditions, which helps remove dirt and dust from the mining insert being treated, reducing health hazards. The second hardfacing treatment can be high energy tumbling.
[0042] The lining of the tumbler may need to be modified so that it can withstand the high temperatures at which the process takes place.
[0043] In one embodiment, the surface hardening process is carried out under dry conditions.
[0044] In one embodiment, all or a portion of the heat is generated by friction between the insert and any media added in the tumbling process.
[0045] In one embodiment, HV3 η is at least 1450HV3, preferably at least 1460HV3, more preferably at least 1470HV3, more preferably greater than 1490HV3, more preferably greater than 1500HV3. η is considered to be the hardness of the η-phase core, equivalent to the bulk of the insert.
[0046] Hardness measurements are carried out using a programmable hardness tester KB30S by KB Pruftechnik GmbH, calibrated against test blocks HV1, HV3, HV20, HV30 and HV100 issued by the Euro Products Calibration Laboratory, UK. Hardness is measured according to ISO EN6507-01.
[0047] HV3 measurements were performed in the following manner. -Scan the edge of the sample. -Program the hardness tester to make an indentation at a specified distance from the edge of the specimen. -Perform an indentation with a 3kg load at all programmed coordinates. The computer moves the stage to each coordinate, positions the microscope over each indentation, auto-adjusts the light, auto-focuses, and automatically measures the size of each indentation. - The user inspects all photos of the indentations for focus and other things that may confuse the results.
[0048] In one embodiment of the present invention, the cemented carbide is uncoated. EXAMPLES
[0049] Example 1 - Starting materials and tumbling conditions Mining inserts with the following (sintered) compositions were tested: TIFF2024526124000002.tif45170
[0050] All the cemented carbide inserts were produced using WC powder particle sizes whose FSSS was measured to be between 5 and 18 μm before grinding. The WC and Co powders were milled in a ball mill under wet conditions using ethanol with the addition of 2 wt% polyethylene glycol (PEG8000) and cemented carbide grinding bodies as an organic binder (pressing agent). After grinding, the mixture was spray dried under N2 atmosphere and then uniaxially pressed to produce mined inserts with a size of about 18 mm outer diameter (OD) and about 32 mm height, weighing about 54 g, and a spherical dome at the top ("cutting edge") for samples A, C, and D, respectively. The insert for sample B had an OD of 10 mm. The inserts were then pre-sintered in N2 gas before being heat treated under a carbonizing atmosphere. After sintering the samples had an η-phase content of about 4 wt% in the η-phase core. An example of a sintering method is further detailed in EP 0182759.
[0051] Comparative Sample A was wet tumbled at room temperature in a standard centrifugal tumbler (i.e., low energy, not HET), and Comparative Sample B was tumbled at room temperature using HET.
[0052] For samples C and D of the present invention, a "hot shake" method was used to replicate the HET at high temperature on a laboratory scale. The hot shake method uses a commercial paint shaker, Corob™ Simple Shake 90, with a maximum load of 40 kg and a maximum shaking frequency of 65 Hz. The "hot shake" method was performed on a batch of 20 mining inserts at a frequency of 45 Hz. Approximately 1000 grams or 50 inserts and 4.0 kg of carbide media (1490 balls of approximately 7 mm) were placed in a cylindrical steel container with an inner diameter of 10 cm and an internal height of 12 cm, and filled to 2 / 3 of its height. The steel cylinder with the mining inserts was heated to a high temperature of 300° C. in a furnace together with the media, and the mining inserts were held at the target temperature for 120 minutes. After heating, the steel cylinder was transferred directly to the paint shaker and immediately shaken for 9 minutes. The transition time between the furnaces before the shaker started was less than 20 seconds. The media was made of cemented carbide grade H10F with 10 wt% Co, 0.5 wt% Cr, and 89.5 wt% WC, resulting in a sintered HV20 of about 1600. In the results table, the samples treated by this method are referred to as "Dry Shaking at 300°C", where the shaking was performed in dry conditions, i.e., no water was added to the shaking. Both inventive cases (C and D) were then subjected to a second tumbling step under wet conditions, at room temperature, but with different tumbling intensities. The second tumbling step for sample C used the same conditions as the hot shaking method described above, except that no heating or furnace step was performed before shaking in order to achieve a very strong wet tumbling effect close to room temperature, and 100 ml of water was added to the steel cylinder before tumbling. The second tumbling step for Sample D was performed using a standard centrifugal tumbler Rasler FKS04 with a disk size of 350 mm at 300 RPM (near maximum RPM) under wet conditions for 50 minutes.
[0053] The temperatures specified for the case hardening process are starting temperatures. For batches processed at a starting temperature of 25°C, if water is added to the process, the temperature is not expected to increase significantly as the samples are processed.
[0054] Example 2 - Edge Damage For highest yields, it is important that there is little, and preferably no, damage to the edges of the mining inserts after tumbling.
[0055] To compare the yield of good quality mining inserts when the surface hardening treatment is performed at room temperature versus elevated temperature, batches of 20 mining inserts of each specimen type were visually inspected for damage after tumbling. Mining inserts were counted as damaged if chipping exceeded approximately 1 mm in length or if chipping reached the ground cylindrical surface where the center of the insert was not present. The percentage of damaged inserts is shown in Table 2. TIFF2024526124000003.tif36170
[0056] The results in Table 2 show that when the surface hardening treatment is performed at elevated temperatures, the amount of edge damage to the mining inserts is reduced. The results in Table 2 show that the rate of edge damage to the inserts of sample B was so high that it was not a viable process for use in production, while the yields of samples C and D of the present invention were comparable to those achieved using standard centrifugal tumbling.
[0057] Example 3 - Insert Compression Test The insert compression test method involves compressing a drill bit insert between two parallel, planar, rigid counter faces at a constant displacement rate until the insert breaks. A test fixture based on the standard ISO4506:2017(E) "Hardmetals-Compression test" was used with cemented carbide anvils with a hardness of over 2000HV, but the test method itself was adapted for testing the toughness of rock drilling inserts. The fixture was mounted on an Instron 5989 test frame.
[0058] The loading axis was identical to the axis of rotational symmetry of the insert. The counter faces of the fixture met the parallelism required by the standard ISO4506:2017(E), i.e. a maximum deviation of 0.5 μm / mm. The tested inserts were loaded at a constant crosshead displacement rate equal to 0.6 mm / min until failure, while load-displacement curves were recorded. The suitability of the test rig and the test fixture was subtracted from the measured load-displacement curves before the test evaluation. Five inserts were tested per specimen type. Before each test, the counter faces were inspected for damage. It was determined that the failure of the insert occurred when the measured load dropped suddenly by at least 1000 N. Subsequent inspection of the tested inserts confirmed that this coincided in all cases with the appearance of a crack visible to the naked eye. The material strength was characterized by the total absorbed deformation energy until fracture. The total fracture energy in Joules (J) required to crush the specimens is given in Table 3 below. TIFF2024526124000004.tif31170
[0059] Table 3 shows that significantly higher fracture toughness is achieved from Samples C and D of the present invention.
[0060] Example 4 - Hardness Measurement HV3 hardness was measured on the polished cross-section inserts at depths of 0.3, 0.8, 1.3, 1.8.2.3, 2.8, 3.3, 3.8, 4.3, 4.8, 5.3, 5.8, 6.3, and 6.8 mm below the edge. Figure 1 shows the indentation hardness and the location of the hardness measurements for sample C. The profile hardness HV3p is the average of the HV3 hardness measurements taken 0.3 mm below the tumbling surface over the upper non-cylindrical part of the insert as shown in Figure 1. The η-phase core hardness HV3η is the average of the HV3 hardness measurements taken in the core η-phase region as shown in Figure 1. Table 4 summarizes the average HV3η measurements and shows that HV3p-HV3η is greater for the inventive samples. TIFF2024526124000005.tif31170
[0061] FIG. 2 shows the HV3 profile through the center of the insert from tip to bottom using software Origin from OriginLab Corporation.
[0062] Example 4 - Field Testing Down-the-hole (DTH) rock drill bits φ229 mm with 18 mm DP65™ inserts were tested, where the inserts were either treated with low-temperature wet high-energy tumbling (sample B - comparative sample) or with dry high-temperature high-energy tumbling at 300°C (sample C - inventive sample). Tumbling for both sets of inserts was performed in the same equipment with the same conditions such as tumbling intensity and tumbling time. The comparative sample was tumbled according to industry standards using about 5 kg of carbide inserts and 100 ml of water-based grinding fluid in a steel tumbling drum. The inventive sample was tumbled by pre-heating about 5 kg of carbide inserts containing a tumbling steel drum to 300°C, followed by direct high-energy tumbling by placing the filled hot tumbling drum into the tumbler.
[0063] Each DTH bit consisted of 12 inserts in the outermost gauge insert row measuring 32.5 mm in height and 108 g in mass, and 17 inserts in the remaining front row measuring 27.5 mm in height and 89 g in mass.
[0064] The bit was tested on rocks consisting mostly of diorite and dolerite, where the compressive strength of the rocks ranges from 280-350 MPA. Dolerite is harder than diorite and typically results in more insert failures, especially in the gauge column, which is the weakest point of the jackhammer bit. Improving the gauge insert strength will improve tool life in terms of metres drilled.
[0065] Eight comparative samples and nine inventive samples were tested, and the results are shown in Table 5 below. TIFF2024526124000006.tif80170
[0066] It can be seen that the average bit life increased from 482m to 557m, which is a 16% increase in drill life, and the average number of gage insert breakages decreased from 7.5 to 5.9, which is a 21% decrease.
Claims
1. 1. A method for treating a cemented carbide insert for rock drilling and mineral cutting, comprising a cemented carbide core and a surface zone of cemented carbide surrounding said core, characterized in that both the surface region and the core contain WC (α phase) with a binder phase (β phase) based on at least one of cobalt, nickel or iron, the core further contains eta phase, the surface zone is free of eta phase, an inner part of the surface zone located next to the core has a binder phase content higher than the nominal content of the binder phase in the cemented carbide body, the binder phase content gradually increasing in the surface zone in a direction towards the core by at least 1.2 times compared to the nominal content of the binder phase of the cemented carbide body, the insert is subjected to a surface hardening process, the mining insert is heated to a temperature of 50° C. or higher before the surface hardening process, the surface hardening process is then carried out at an elevated temperature of 50° C. or higher, the surface hardening treatment being tumbling.
2. 2. The method according to claim 1, wherein the cemented carbide comprises the hard constituents in a metal binder phase, the content of the metal binder phase in the cemented carbide being 3-30 wt. %, preferably 5-15 wt. %.
3. 2. The method of claim 1, wherein the metallic binder phase comprises at least 80 wt. % of one or more metallic elements selected from Co, Ni, and Fe.
4. The method of claim 1, wherein the cemented carbide additionally comprises Cr in an amount such that the Cr / binder mass ratio is between 0.043 and 0.
19.
5. 2. The method according to claim 1, wherein the content of the binder phase in the surface zone increases towards the core by 1.4 to 2.5 times the nominal content of the binder phase.
6. 10. The method of claim 1, wherein the insert is tumbled with media, and the media is further heated to a temperature of 50°C or greater prior to and during tumbling.
7. The method of claim 1 , wherein the mining insert is maintained heated during the hardfacing process.
8. 10. The method of claim 1, wherein after the mining insert is subjected to a hardfacing process at elevated temperature, the mining insert is subjected to a second hardfacing process at room temperature.
9. The tumbling process is a "high energy tumbling" process, and after tumbling, the uniform cemented carbide mining inserts are ΔHV3%≧9.72−0.00543*HV3 bulk and ΔHV3% is the percentage difference between the HV3 measurement at 0.3 mm from the surface and the HV3 measurement in the bulk.
10. The method of claim 1 , wherein the surface hardening process is carried out under dry conditions.
11. 13. A cemented carbide insert for rock and mineral cutting produced by the method disclosed in claim 1.
12. A cemented carbide insert for rock drilling and mineral cutting, comprising a cemented carbide core and a surface zone of cemented carbide surrounding said core, both the surface zone and the core containing WC (α-phase) with a binder phase (β-phase) based on at least one of cobalt, nickel or iron, the core further containing η-phase, the surface zone being free of η-phase, an inner part of the surface zone located next to the core having a binder phase content greater than the nominal binder phase content in the cemented carbide body, the binder phase content gradually increasing in the surface zone in a direction towards the core by at least 1.2 times compared to the nominal binder phase content of the cemented carbide body, the cemented carbide insert having a profile hardness HV3p measured 0.3 mm from the surface over an upper non-cylindrical part of the cemented carbide insert, and an η-phase core hardness HV3η which is the average of the HV3 hardness measurements taken in the core η-phase region, p -HV3 η The cemented carbide insert is characterized in that the tensile strength is greater than 20.
13. HV3 η 13. The cemented carbide insert according to claim 12, wherein the hardness is at least 1450 HV3.